2021
DOI: 10.1186/s12920-021-01129-0
|View full text |Cite
|
Sign up to set email alerts
|

The genetic susceptibility profile of type 2 diabetes and reflection of its possible role related to reproductive dysfunctions in the southern Indian population of Hyderabad

Abstract: Background The genetic association studies of type 2 diabetes mellitus (T2DM) hitherto undertaken among the Indian populations are grossly inadequate representation of the ethnic and geographic heterogeneity of the country. In view of this and due to the inconsistent nature of the results of genetic association studies, it would be prudent to undertake large scale studies in different regions of India considering wide spectrum of variants from the relevant pathophysiological pathways. Given the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 82 publications
1
4
0
Order By: Relevance
“…In line with our findings, a series of studies have reported significant correlations of FTO rs9939609 and rs17817449 polymorphisms with the risk of T2DM and dyslipidemia (24,28,29,33,(46)(47)(48)(49)(50)(51). Younus et al conducted a case-control study to investigate the impact of the rs9939609 and rs17817449 polymorphisms on the development of T2DM in a sample of obese Iraqis, and found that the minor alleles of both variants are associated with an increased risk of T2DM (33).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In line with our findings, a series of studies have reported significant correlations of FTO rs9939609 and rs17817449 polymorphisms with the risk of T2DM and dyslipidemia (24,28,29,33,(46)(47)(48)(49)(50)(51). Younus et al conducted a case-control study to investigate the impact of the rs9939609 and rs17817449 polymorphisms on the development of T2DM in a sample of obese Iraqis, and found that the minor alleles of both variants are associated with an increased risk of T2DM (33).…”
Section: Discussionsupporting
confidence: 85%
“…Younus et al conducted a case-control study to investigate the impact of the rs9939609 and rs17817449 polymorphisms on the development of T2DM in a sample of obese Iraqis, and found that the minor alleles of both variants are associated with an increased risk of T2DM (33). In addition, the significant relation between the rs9939609 and rs17817449 polymorphisms and T2DM risk was reported in Vietnamese (28), Indians (29), Egyptians (47) and Czechs (48) and Pakistanis (51). Sierra-Ruelas and teammates explored the association of the rs9939609 variant with serum lipids among Mexican adults, and found that the A allele carriers had significantly higher levels of TC and LDL-C (24).…”
Section: Discussionmentioning
confidence: 99%
“…The results analysis showed that the average age for the controls group was 54 and for patient groups were as follows: T2D (53), CHD (52), and T2D + CHD (53). Consequently, the different comparison of the mean age of both groups revealed no statistically significant differences between the groups: control, T2D, CHD, and T2D + CHD.…”
Section: General Descriptive Resultsmentioning
confidence: 87%
“…Phase 1 was conducted to determine the T2D risk genes in the Malaysian population. Previously, it was proved that the T2D risk genes were different in geographically distinct populations [52,53]. Furthermore, phase two was conducted to subtract coexisting genes in phases one and two from phase one because these dysregulated genes were intrinsically CHD risk genes.…”
Section: Discussionmentioning
confidence: 99%
“…Using the whole transcriptome RNAseq, the same group further investigated the peripheral subcutaneous adipose tissue of Asian Indians and found altered lipid, glucose, and protein metabolisms; adipogenesis defects; and inflammation associated with T2DM [ 183 ]. Using the AGENA MassARRAYiPLEX™ platform, Irgam et al recently identified seven significant SNPs (s2241766-G (ADIPOQ), rs6494730-T (FEM1B), rs1799817-A, rs2059806-T (INSR), rs11745088-C (FST), rs9939609-A, and rs9940128-A (FTO)) associated with T2DM in a southern Asian Indian population of 500 cases [ 184 ].…”
Section: The Potential Role Of Multi-omics and Single Cell-based Tech...mentioning
confidence: 99%